Delta-catenin attenuates medulloblastoma cell invasion by targeting EMT pathway - Hu, Yuanjun; Zhu, Sihan; Xu, Rizhen; Wang, Manxia; Chen, Furong; Zhang, Zeshun; Feng, Binghong; Wang, Jian; Chen, Zhongping; Wang, Jing (Frontiers in Genetics, 2022)
Medulloblastoma is the most common malignant pediatric central nervous system tumor. Although its prognosis has been improved enormously by the combination of surgery, radiotherapy, and chemotherapy, it still may progress via invasion and dissemination. This study mainly aimed to investigate molecular mechanisms of medulloblastoma invasion. The differentially expressed genes were firstly calculated from the mRNA expression profiles of medulloblastoma patients in the Gene Expression Omnibus database and then filtered by intersecting with brain specific proteins in the Uniprot. Delta-catenin was identified and further analyzed its expression with clinical characteristics such as prognosis, molecular subgroup, and metastasis. We found that delta-catenin was highly upregulated in tumor tissues compared to normal tissues from medulloblastoma patients in five independent, nonoverlapping cohort. Delta-catenin expression was upregulated in WNT subgroup, and significantly correlated with better prognosis, and associated with metastasis through GEO database analysis. Functional assays indicated that delta-catenin attenuated medulloblastoma cell invasion and migration through interacting with epithelial-mesenchymal transition pathway. In summary, delta-catenin, which attenuates medulloblastoma cell invasion by inhibiting epithelial-mesenchymal transition pathway, might be a positive predictor for prognosis of medulloblastoma patients.